Fenomena Dakwah Digital Tematik (Studi Kasus Akun Instagram Romo Andreas Subekti dan Habib Husein Ja’far Al-Hadar) - Tati Aswiandini; Wasil Wasil (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
The research analyzes the digital da'wah strategies used by two religious figures, Romo Andreas Subekti and Habib Husein Ja’far Al-Hadar, who utilize social media platforms, particularly Instagram, to deliver their digital da'wah. This research was conducted through various data collection methods, including observation, interviews, literature studies, and documentation. The results of this study show that Habib Husein Ja’far Al-Hadar focuses on spreading religious messages through content such as quotes, short sermons, and inspirational videos accompanied by invitations to dialogue and ask questions. Conversely, Romo Andreas Subekti uses Instagram for personal reflections, daily life stories, and practical religious guidance, supported by engaging visuals and narratives. Both figures utilize Instagram as a medium for da'wah in ways that align with their character and audience. The researcher also found that user interactions, such as comments and direct messages, play an essential role in strengthening relationships between religious figures and their followers on social media. These findings provide insights into how social media can be effectively used in the context of contemporary da'wah and suggest strategic steps to enhance the impact of digital da'wah.